Influence of livelihoods on climate change adaptation for smallholder farmers in the Mekong Delta Vietnam. Issue 3 (4th May 2018) - Brown, Peter R.; Tuan, Vo Van; Nhan, Dang Kieu; Dung, Le Canh; Ward, John
ABSTRACT: Farmers in the Vietnamese Mekong Delta face a wide range of climate-related and hydrological factors which threaten rice production. Smallholder farmers must adapt to climate change to sustain rice production as their central and most important livelihood activity. A sample was stratified across agro-ecological areas in the Delta affected by flooding, alluvial soils, acid sulphate soils, and saline water intrusion and by derived farmer typologies. A rural livelihoods approach was used in focus group discussions and in-depth interviews to identify and enumerate enabling and constraining adaptation factors. Smallholders experienced diverse natural hazards such as floods, abnormal rains, high temperatures, water scarcity, and salinity intrusion specific to the agro-ecological areas. Adaptation was constrained by labour shortages, water quality, topography, access to combine harvesters, transportation infrastructure, dryers and household savings. Adaptation was enabled by farming techniques and experience, cooperative groups, water quantity, access to information, and ability to purchase agro-chemicals through credit. Small farmers (< 1 ha) were more constrained than large farmers (> 1 ha) who had an expanded livelihood asset base. A range of policy implications are discussed, but adaptation is not just about technological fixes but requires overall improvements in a range of human, social and financial components.